Strategi Guru PAI dalam Mengintegrasikan Media Digital Pada Pembelajaran di SMK PGRI 4 Pasuruan - Nurul Lailatul Maulydyah; Jakaria Umro; Nurhasan Nurhasan (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This research is motivated by the rapid development of information technology, which requires teachers to be able to adapt and utilize digital media as a means of supporting effective and engaging learning for students. The purpose of this study is to describe the strategies used by Islamic Religious Education (PAI) teachers in integrating digital media into the learning process at SMK PGRI 4 Pasuruan City, to determine what inhibiting and supporting factors they experienced during the implementation of digital media in learning. This research method uses a descriptive qualitative approach with a case study research type. Data collection techniques were carried out through observation, interviews, and documentation. The analysis techniques used were data reduction, presentation, and conclusions. In checking the validity of the data, the researcher used triangulation techniques. The results of the study indicate that Islamic Religious Education (PAI) teachers at SMK PGRI 4 Pasuruan City have implemented various strategies in integrating digital media, such as the use of learning videos, online learning platforms (e-learning), and interactive presentation applications. These strategies not only increase student participation but also help in delivering more varied and contextual material. Despite several obstacles, such as limited facilities and technical skills, teachers continue to innovate to create a conducive and adaptive learning environment. This study concludes that the integration of digital media by Islamic Religious Education teachers positively contributes to the effectiveness of learning in vocational high schools.